Transcultural Adaptation and Validation of Persian Version of Celiac Disease Questionnaire (CDQ); A Specific Questionnaire to Measure Quality of Life of Iranian Patients: - Barzegar, Farnoush; Pourhoseingholi, Mohamad Amin; Rostami-Nejad, Mohammad; Gholizadeh, Sepideh; Malekpour, Mohammad Reza; Sadeghi, Amir; Rostami, Kamran; Maleki, Iradj; Shahbazi, Shahin; Emami, Mohammad Hassan; et al. (Galen Medical Journal, 2018)
Background: The assessment of health-related quality of life has become an important primary or secondary outcome measure in clinical and epidemiologic studies. The aim of this study was to validate a Persian version of Celiac Disease Questionnaire (CDQ) for Celiac disease (CD) among Iranian patients. Materials and Methods: The English version of the CDQ adapted to the Persian language by a forward-backward translation by 3 professional bilingual translators (1 medical, 2 nonmedical). The content validity of translated questionnaire were studied by 5 experts who complete the validity form regarding the questionnaire. Then in a pilot study, translated CDQ completed by 81 CD patients who referred to Taleghani Hospital, Tehran. For assessing the validity and reliability of the questionnaire, confirmatory factor analysis and Cronbach’s alpha coefficient have been done, using Lisrel and SPSS software. Results: Of 81 CD patients entered to this study with mean age of 30.54 years old, 71.6% were female. Also, 56.8% were married and 45.7% were high educated. The mean of CDQ total score was 119.18±34. The calculated Cronbach’s alpha coefficient for CDQ questionnaire was 0.9. Also, for each subgroups the Cronbach’s alpha coefficient were calculated as the following; emotion: 0.92, Social: 0.89, Worries: 0.73, Gastrointestinal: 0.78. Confirmatory factor analysis indicated that all questions could be remain in questionnaire respectively. Conclusion: The reliability of the Persian version of CDQ was excellent with Cronbach’s alpha coefficients and Persian version of CDQ retains the psychometric properties of the original instrument and should be useful to assess outcome in studies and clinical trials involving Iranian patients with CD. [GMJ.2018;7:e1106]